Integrative Assessment of Depression Levels in Final Semester Students: A Quantitative-qualitative Approach for Enhanced Mental Health Evaluation and Academic Support - Paul Grievson; Jessen Weinberger (IHSA Institute, 2023)
This research endeavors to assess depression levels among final semester students, employing a comprehensive approach that amalgamates quantitative scores from standardized psychological assessments with qualitative insights garnered through structured interviews. The study aims to provide a nuanced evaluation framework that captures the multifaceted nature of mental health during this critical phase of academic life. Utilizing a weighted sum model, this investigation synthesizes quantitative symptomatology scores obtained from standardized assessments, normalized to a scale of 0 to 1, with qualitative insights rated on a scale of 1 to 10. Equal weightage (0.5 each) is assigned to both dimensions to facilitate a balanced evaluation. Data from three hypothetical final semester students illustrate the implementation of this approach, yielding overall depression levels reflective of the combined quantitative and qualitative assessments. The outcomes highlight the significance of this combined assessment approach in delineating depression levels. The research emphasizes the intricate interplay between quantitative symptomatology and individual narratives, showcasing the importance of contextual nuances in mental health evaluations. These findings signal a pathway for academic institutions to develop tailored interventions, fostering supportive environments that prioritize mental well-being alongside academic success.